The Extent of Alcohol-Related Problems Among College and University Students in Norway Prior to and During the COVID-19 Pandemic - Heradstveit, Ove; Sivertsen, Børge; Lønning, Kari-Jussie; Skogen, Jens Christoffer (Frontiers in Public Health, 2022)
Aim: To provide estimates of the distribution of alcohol-related problems in a national sample of college and university students in 2021, i.e., during the COVID-19 pandemic, in comparison with pre-pandemic data from 2018. Design: Longitudinal data from linkage of two recent national health surveys from 2018 and 2021. Setting: Students in higher education in Norway (the SHoT-study). Participants: 8,287 fulltime students (72.5% women; 27.6% men) that were 18 years or more at the time of the first survey in 2018, and 21 years or more at the time of the second survey in 2021. Measurements: The Alcohol Use Disorders Identification Test (AUDIT) was used to assess potential alcohol-related problems. Findings: 37.0% of male students and 24.1% of female students reported either risky, harmful, or dependent alcohol use in 2021, compared with 55.0% of male students and 43.6% of female students in 2018. This decrease in alcohol-related problems was most pronounced for dependent alcohol use, where we observed a 57% relative reduction among male students (from 3.5% in 2018 to 1.5% in 2021) and a 64% relative reduction among female students (from 1.4% in 2018 to 0.5% in 2021). Conclusions: The present study demonstrated a sharp decline in alcohol-related problems among students during the COVID-19 pandemic, that were present across gender, age groups, and geographical study locations. Universal preventive measures to limit students’ alcohol use should be considered when restrictions related to the pandemic is lifted.